Current research in empirical therapy for febrile neutropenia in cancer patients: what should be necessary and what is going on. (September 2013) - Castagnola, Elio; Mikulska, Malgorzata; Barabino, Paola; Lorenzi, Ines; Haupt, Riccardo; Viscoli, Claudio
Abstract : Introduction: Fever is an important complication in neutropenic patients and standard of care calls for empirical broad-spectrum antibiotics, followed by 'empirical' antifungal therapy in persisting fever. Emergence of infections due to resistant bacteria, especially Gram-negatives, and usefulness of empirical antifungal therapy represent the major concerns in this field. Areas covered: Clinical trials registered in 5 international databases were referred for randomized clinical trials (RCTs) of empirical antibacterial therapy or empirical antifungal therapy in neutropenic cancer patients. The majority of RCTs compared antibiotics without major differences in the spectrum of activity, especially in the wake of the present epidemiology with an increase of infections and mortality due to resistant Gram-negatives; oral therapy and home care were analyzed in 3 RCTs. As regards empirical antifungal therapy, 1 ongoing study is comparing 'standard' empirical treatment vs diagnostic-driven approach. Expert opinion: In an era of increasing antibiotic resistance the comparison of different strategies more than that of different drugs will probably represent the future in studies in this field. The next future will tell us if a diagnostic-driven approach is safe for fungal infections, or if we should continue to treat them only on the basis of the persistence of febrile neutropenia.